Heat Transfer and Flow Characteristics Inside Droplet Formed on Water Surface. Issue 11 (16th June 2020) - Al-Sharafi, Abdullah; Yilbas, Bekir Sami
Abstract: Dynamics and heat transfer of a silicone oil droplet formed on a water surface are investigated. The silicone oil droplet is heated by the water in a constant temperature container. Temperature and velocity fields inside the droplet are simulated in line with the experimental conditions. The influence of the droplet volume on the flow and heat transfer characteristics is also incorporated in the analysis. The oil droplet pinning and its geometric features for different droplet volumes are examined. Temperature predictions are validated with a thermal camera data. It is found that temperature predictions agree well with the thermal camera data. The constant temperature heating of the water container wall gives rise to two counter rotating circulation cells inside the water, which in turn modifies temperature and flow fields in the water. The flow direction occurs from the droplet top region towards the droplet–water interface. The heated fluid in the region close to the droplet–water interface is carried by the flow current to the droplet sides giving rise to temperature increase in these regions. The values of the Bond number attains greater than unity. The Nusselt and the Bond numbers increase with the droplet volume.